Division and square root in fixed point microprocessors - Mok, Lu Min. (2008)
In this project, the different methods of performing division and the square root function were implemented and compared using C programs. The algorithms were then compared and simulated on Matlab paying particular attention to the effects of changing the finite word size (8, 16 and 32 bit ) for numerical representation errors of the final results.